One-dimensional van der Waals stacked p-type crystal Ta2Pt3Se8for nanoscale electronics - Jeong, Byung Joo; Choi, Kyung Hwan; Jeon, Jiho; Yoon, Sang Ok; Chung, You Kyoung; Sung, Dongchul; Chae, Sudong; Oh, Seungbae; Kim, Bum Jun; Lee, Sang Hoon; Woo, Chaeheon; Kim, Tae Yeong; et al. (Nanoscale, 2021)
Recently, ternary transition metal chalcogenides Ta2X3Se8 (X = Pd or Pt) have attracted great interest as a class of emerging one-dimensional (1D) van der Waals (vdW) materials. In particular, Ta2Pd3Se8 has been actively studied owing to its excellent charge transport properties as an n-type semiconductor and ultralong ballistic phonon transport properties. Compared to subsequent studies on the Pd-containing material, Ta2Pt3Se8, another member of this class of materials has been considerably less explored despite its promising electrical properties as a p-type semiconductor. Herein, we demonstrate the electrical properties of Ta2Pt3Se8 as a promising channel material for nanoelectronic applications. High-quality bulk Ta2Pt3Se8 single crystals were successfully synthesized by a one-step vapor transport reaction. Scanning Kelvin probe microscopy measurements were used to investigate the surface potential difference and work function of the Ta2Pt3Se8 nanoribbons of various thicknesses. Field-effect transistors fabricated on exfoliated Ta2Pt3Se8 nanoribbons exhibited moderate p-type transport properties with a maximum hole mobility of 5 cm2 V-1 s-1 and an Ion/Ioff ratio of >104. Furthermore, the charge transport mechanism of Ta2Pt3Se8 was analyzed by temperature-dependent transport measurements in the temperature range from 90 to 320 K. To include Ta2Pt3Se8 in a building block for modern 1D electronics, we demonstrate p-n junction characteristics using the electron beam doping method. This journal is
Keywords: Ballistic phonons; Charge transport properties; N-type semiconductors; Nanoscale electronics; One-dimensional; P-type; Phonon transport; Transition metal chalcogenides; Transition-metal chalcogenides; Van der Waal